1976
DOI: 10.1154/s0376030800011940
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction Studies of Shocked Lunar Analogs

Abstract: X-ray diffractometer studies of single-crystal quartz and orthoclase reveal the peak shock pressure experienced by the samples. This procedure may facilitate tapid, quantitative interpretation of the peak shock pressures experienced by materials occurring in lunar or terrestrial impact structures. Shocked specimens were obtained from the NASA 20 mm flat-plate accelerator at Johnson Space Center, Houston. Orthoclase single crystals were shocked normal to the (001) plane at pressure intervals between 0 and 297 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This progressive loss of long-range order is seen in X-ray diffraction patterns of the mineral (Heymann, 1967;Taylor and Heymann, 1969). Mineralogical studies on laboratory-and naturally shocked olivines have been reported by Carter et al (1968), Mueller and Hornemann (1969), James (1969), Short (1969), Von Engelhardt et al (1970), Levi-Donatti (1971), Sclar and Morzenti (1971), Hoerz and Quaide (1973), Ashworth and Barber (1975), Snee and Ahrens (1975), Lally et al (1976), Hanss et al (1977Hanss et al ( , 1978, Reimold and Steffler (1978), Bauer (1978Bauer ( , 1979 and Syono et al (1981). Jeanloz and Ahrens (1977), Jeanloz et al (1977), and Bauer(1978) have interpreted high-pressure Hugoniot and other data from shocked olivines to mean that optical isotropic olivine ("olivine glass") forms, but also that a distinct spinel phase of olivine may form.…”
Section: Introductionmentioning
confidence: 93%
“…This progressive loss of long-range order is seen in X-ray diffraction patterns of the mineral (Heymann, 1967;Taylor and Heymann, 1969). Mineralogical studies on laboratory-and naturally shocked olivines have been reported by Carter et al (1968), Mueller and Hornemann (1969), James (1969), Short (1969), Von Engelhardt et al (1970), Levi-Donatti (1971), Sclar and Morzenti (1971), Hoerz and Quaide (1973), Ashworth and Barber (1975), Snee and Ahrens (1975), Lally et al (1976), Hanss et al (1977Hanss et al ( , 1978, Reimold and Steffler (1978), Bauer (1978Bauer ( , 1979 and Syono et al (1981). Jeanloz and Ahrens (1977), Jeanloz et al (1977), and Bauer(1978) have interpreted high-pressure Hugoniot and other data from shocked olivines to mean that optical isotropic olivine ("olivine glass") forms, but also that a distinct spinel phase of olivine may form.…”
Section: Introductionmentioning
confidence: 93%